A Bacterial Effector Protein Hijacks Plant Metabolism to Support Pathogen Nutrition. - Xian, Liu; Yu, Gang; Wei, Yali; Rufián Plaza, José Sebastián; Li, Yansha; Zhuang, Haiyan; Xue, Hao; Morcillo, Rafael J; Macho, Alberto P (Cell Press, 2020)
Many bacterial plant pathogens employ a type III secretion system to inject effector proteins within plant cells to suppress plant immunity. Whether and how effector proteins also co-opt plant metabolism to support extensive bacterial replication remains an open question. Here, we show that Ralstonia solanacearum, the causal agent of bacterial wilt disease, secretes the effector protein RipI, which interacts with plant glutamate decarboxylases (GADs) to alter plant metabolism and support bacterial growth. GADs are activated by calmodulin and catalyze the biosynthesis of gamma-aminobutyric acid (GABA), an important signaling molecule in plants and animals. RipI promotes the interaction of GADs with calmodulin, enhancing the production of GABA. R. solanacearum is able to replicate efficiently using GABA as a nutrient, and both RipI and plant GABA contribute to a successful infection. This work reveals a pathogenic strategy to hijack plant metabolism for the biosynthesis of nutrients that support microbial growth during plant colonization.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/6581
Keywords: Plantas - Metabolismo; Bacterias fitopatógenas; RipI; Ralstonia solanacearum; GABA; Effectors